PENGARUH PENERAPAN MEDIA PEMBELAJARAN POP-UP BOOK TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Simbolon, Marlina Eliyanti; Fitriyani, Yani (Institut Hindu Dharma Negeri Denpasar, 2021)
This research is motivated by the low student learning outcomes. The purpose of this study was to determine the differences in post-test results in a class using Pop-up book learning media with a class that did not use Pop-up book learning media and to find out the difference in the improvement of student learning outcomes in science class II SDN 1 Winduhaji. The method used in this research is a quasi-experimental design nonequivalent control group design. The research subjects consisted of two classes, class A consisting of 23 students as the experimental class and class B consisting of 23 students as the control class. The research instrument used a written test in the form of multiple choice questions. Furthermore, analysis of instruments and data analysis is carried out. Data analysis in the control class and experimental class using SPSS version 22 assistance. Data analysis in the experimental class and control class shows that the sig (2-tailed) value is 0.000 <0.05. So the results of the study show that there are posttest differences in student learning outcomes between students who use Pop-up book learning media and students who don't use Pop-up book learning media. Then there is a difference in the increase in student learning outcomes in classes using Pop-up book learning media with an increase in student learning outcomes in classes that do not use Pop-up book learning media. From these data it can be explained that the Pop-up book learning media has a significant effect on student learning outcomes and can be used as an alternative learning media for teachers in improving learning outcomes.